2017
DOI: 10.1159/000478266
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Classification of Prognostic Factors Based on Pathological Stage and Tumor Regression Grade in Patients with Rectal Cancer Who Receive Preoperative Chemoradiotherapy

Abstract: Objective: The histologic response to neoadjuvant chemoradiotherapy (CRT) has been intimately related to outcomes in locally advanced rectal cancer. However, reliable prognostic factors have yet to be established. Subjects and Methods: The study group comprised 198 patients with locally advanced rectal cancer who received CRT. A modified classification based on the combination of ypStage and tumor regression grade (TRG) was developed. ypStage II with TRG 2 was classified as ypTRGstage IIA, and ypStage II with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Although several studies have evaluated the prognostic significance of partial or near-complete response, the results are conflicting [ 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. So far, only a few studies have examined the potential complementary value of TRG with the American Joint Committee on Cancer (AJCC) TNM pathologic staging system in predicting recurrence or survival [ 7 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have evaluated the prognostic significance of partial or near-complete response, the results are conflicting [ 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. So far, only a few studies have examined the potential complementary value of TRG with the American Joint Committee on Cancer (AJCC) TNM pathologic staging system in predicting recurrence or survival [ 7 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Huh et al compared the prognostic signi cance of TRG in patients with rectal cancer after preoperative CRT and found better 5-year overall survival (OS) and DFS in patients with TRG0 (complete response) than in those with TRG1 (moderate), and TRG2-3 (minimal-poor)(4). Suzuki et al used a modi ed classi cation system based on pathological T (ypT) stage and TRG, and showed that a less advanced stage was independently related to improved DFS (5). Assessment of preoperative TRG after CRT may help to stratify patients according to prognosis so that clinicians can administer the most appropriate preoperative therapy(6).…”
Section: Introductionmentioning
confidence: 99%
“…4 Suzuki et al used a modified classification system based on pathological T (ypT) stage and TRG, and showed that a less advanced stage was independently related to improved DFS. 5 Although the advantage of establishing the preoperative TRG is not clear because this information is provided by the pathology results, it may allow more individualized treatment, such as a non-surgical "watch and wait" approach, because approximately 10 to 30% of rectal cancer patients achieve pCR after CRT. 1,2,[6][7][8] Magnetic resonance imaging (MRI) is now the gold standard for initial staging of rectal cancer and assessment of restaging after neoadjuvant CRT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histological response to CRT has been reported to be closely related to oncologic outcomes [3, 4]. We previously reported that histological changes on hematoxylin-eosin (H-E)-stained specimens together with immunohistochemical expression of p21 and apoptosis in biopsy specimens obtained 7 days after starting nCRT are strong predictors of the response to nCRT [5].…”
Section: Introductionmentioning
confidence: 99%